2023
DOI: 10.1063/5.0174524
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of near-ideal Schottky contacts to Si-doped AlN

C. E. Quiñones,
D. Khachariya,
P. Bagheri
et al.

Abstract: Near-ideal behavior in Schottky contacts to Si-doped AlN was observed as evidenced by a low ideality factor of 1.5 at room temperature. A temperature-independent Schottky barrier height of 1.9 eV was extracted from temperature-dependent I–V measurements. An activation energy of ∼300 meV was observed in the series resistance, which corresponded to the ionization energy of the deep Si donor state. Both Ohmic and Schottky contacts were stable up to 650 °C, with around four orders of magnitude rectification at thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It should be noted that the j eff is in good agreement with the predicted value for Ni Schottky contacts. 15,21) It is worth noting that previous high-voltage AlN SBDs [16][17][18][19][20] failed to demonstrate high j eff close to theoretical values due to deviation from the TE model. Figure 3(b) shows the temperature dependence of j eff and η of the devices.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…It should be noted that the j eff is in good agreement with the predicted value for Ni Schottky contacts. 15,21) It is worth noting that previous high-voltage AlN SBDs [16][17][18][19][20] failed to demonstrate high j eff close to theoretical values due to deviation from the TE model. Figure 3(b) shows the temperature dependence of j eff and η of the devices.…”
mentioning
confidence: 93%
“…4,13,14) Furthermore, Schottky contacts to AlN with ideal Schottky barrier heights (j b ) are difficult to achieve. 15) Recent studies on AlN Schottky barrier diodes (SBDs) have shown promising high-voltage electronic devices. [16][17][18][19][20] However, all these devices suffer from high ideality factors (η) >4.0, indicating the current transport mechanism deviates from the well-known thermionic emission (TE) theory.…”
mentioning
confidence: 99%
See 3 more Smart Citations